2016
DOI: 10.1007/s12325-016-0425-3
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for and Against Use of Non-absorbable, Synthetic Mesh During Pelvic Organ Prolapse Repair, According to the Prolapsed Compartment

Abstract: Awareness and reporting of mesh-related complications of pelvic organ prolapse repairs have increased in recent years. As a result, deciding whether to use a mesh or not has become a difficult task for urogynecologists. Our aim was to summarize reasons for and against the use of mesh in prolapse repair based on a review of relevant literature. Scopus and PubMed databases were searched for papers reporting on the efficacy and safety of native tissue versus non-absorbable, synthetic mesh prolapse repairs. Random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 53 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…Another study reported that de novo SUI was lower in the anterior colporrhaphy group (1.4%, 1/68 patients) compared to the mesh group (8.5%, 6/70 patients). However, the results of another study showed that the recurrence rate for mesh surgery was lower than that of native tissue repair [14]. Another study reported that sexual function may be problematic with vaginal hysterectomy [15].…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that de novo SUI was lower in the anterior colporrhaphy group (1.4%, 1/68 patients) compared to the mesh group (8.5%, 6/70 patients). However, the results of another study showed that the recurrence rate for mesh surgery was lower than that of native tissue repair [14]. Another study reported that sexual function may be problematic with vaginal hysterectomy [15].…”
Section: Discussionmentioning
confidence: 99%
“…The cure figures were subsequently shown: 86.4% in the mesh versus 79.4% in colporrhaphy. 15 Regarding Rudnicki and collaborators, in 2015, they carried out a comparative study in which the cure rates and possible complications in anterior colporrhaphy were observed in relation to transvaginal mesh for prolapse of the anterior vaginal wall, in follow-up of 1 and 3 years through pre-and post-surgical questionnaires and verbal information. This study was carried out through a randomized controlled trial on 138 women over 55 years of age, of which 70 underwent mesh procedures and the remaining 68 underwent colporrhaphy.…”
Section: Comparison and Follow-up Studiesmentioning
confidence: 99%
“…We got access to material in form of polypropylene meshes (MESH), which demonstrated good biocompatibility and promised the possibility of reliable replacement of defective tissues (1). Unfortunately, it was shown that their implantation also comes with certain long-term risks that we have not encountered in classical techniques (2)(3)(4). At present, not only we are in a period of searching for a prudent indication for their use (5), but also, in some countries, there has been a complete ban on the production and distribution of vaginal meshes used in POP surgical treatment and stressed incontinence (6, 7).…”
Section: Introductionmentioning
confidence: 99%